The Study of Behavior and Factors Influencing the Acceptance of Generative Artificial Intelligence in the Business Sector - Srikongphlee, Pichamon; Leejoeiwara, Bussakorn (MBA-KKU Journal, 2026)
This research aims to investigate the behavior and factors influencing the acceptance of Generative Artificial Intelligence (Generative AI) in the business sector in Thailand by applying the Unified Theory of Acceptance and Use of Technology (UTAUT). The four key factors examined included performance expectancy, effort expectancy, social influence, and facilitating conditions. The sample consisted of 400 business professionals who had experience using Generative AI. Data were collected between June and July 2024 through purposive sampling. The data were analyzed using descriptive statistics, including frequency, percentage, mean, and standard deviation. The findings revealed that most respondents were female (50.25%) and aged between 26 and 30 years (35.75%). The majority held a bachelor’s degree (57.50%) and were employed primarily in the service industry (34.00%). A significant portion of respondents used Generative AI at least one to two times per week (59.75%), with Canva being the most frequently used application (53.75%) for advertising content creation (47.00%). Among the factors influencing acceptance, performance expectancy had the highest mean score (Mean = 4.35, S.D. = 0.74), followed by social influence (Mean = 4.17, S.D. = 0.84). The results suggest that organizations should foster supportive environments and enhance employees’ understanding of the benefits of Generative AI to encourage greater acceptance and utilization. Furthermore, training initiatives and organizational support are critical factors in promoting the continued adoption of Generative AI technologies in the business sector.